The effect of third molars on maxillary molar distalisation using a miniscrew-supported 3D® maxillary bimetric distalising arch - Tunçer Nilüfer İrem; Arman-Özçırpıcı Ayça (Sciendo, 2022)
Objectives: The aim of the present study was to investigate the effect of third molars on the efficiency and biomechanics of a novel miniscrew-supported 3D® Maxillary Bimetric Distalising Arch (3D-MBDA).